PEMBELAJARAN COOPERATIVE SCRIPT METAKOGNITIF (CSM) UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA SMP DI MANADO - Warouw, Zusje W.M. (Bioedukasi Jurnal Pendidikan Biologi, 2010)
This research developed learning package, which could improve learning result of the students, Cooperative Script (CS) strategy that was integrated with Metacognitive (M) in the form of self assessing or CSM. Results of such development were experimented to eighth grade students of State Junior High Schools in Manado. Results of the analysis showed that average score of the students who have high-academic capability (AT), and low-academic capability (AR) who applied CSM strategy, have beyond the learning result of the students who have high-academic capability and low-academic capability by applying conventional strategy (Konv):1) average score of the group of CSM-AT strategy, 18,72% higher than Konv-AT, and 26,33% higher than Konv-AR, 2) average score of CSM-AR group, 12,08% higher than Konv-AT, and 19,27% higher than Konv-AR. The improved percentage occurred on CSM-AR group 595,10% for learning result of the studentsÂ Kata kunci: Cooperative Script, Metacognitive, Hasil Belajar